2019
DOI: 10.26434/chemrxiv.9833909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catalytic Enantioselective Pyridine N-Oxidation

Abstract: The catalytic, enantioselective N-oxidation of substituted pyridines is described. The approach is predicated on a biomolecule-inspired catalytic cycle wherein high levels of asymmetric induction are provided by aspartic acid containing peptides as the aspartyl side chain shuttles between free acid and peracid forms. Desymmetrizations of bis(pyridine) substrates bearing a remote pro stereogenic center are demonstrated, presenting a new entry into chiral pyridine frameworks in a heterocycle-rich molecular envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…1−7 However, the long C−S bond would make it more difficult for the catalyst to differentiate the two pyridine rings, which makes the enantiocontrol a great challenge (C−S length: 1.759 Å vs C−C length: 1.520 Å; see Supporting Information, page 66). 10 drawing sulfoximine substituent could reduce the nucleophilicity of the pyridine nitrogen, resulting in lower reactivity. Moreover, the sulfoximine N atom might provide a competitive site for chemoselective oxidation.…”
Section: ■ Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…1−7 However, the long C−S bond would make it more difficult for the catalyst to differentiate the two pyridine rings, which makes the enantiocontrol a great challenge (C−S length: 1.759 Å vs C−C length: 1.520 Å; see Supporting Information, page 66). 10 drawing sulfoximine substituent could reduce the nucleophilicity of the pyridine nitrogen, resulting in lower reactivity. Moreover, the sulfoximine N atom might provide a competitive site for chemoselective oxidation.…”
Section: ■ Introductionmentioning
confidence: 85%
“…8 Therefore, the construction of enantioenriched pyridine derivatives has gained increased attention in the past year. 9, 10 We recently reported that bis(pyridine)s connected to a prochiral carbon center could undergo desymmetrization through selective monooxidation using an aspartic acid (Asp)-peptide catalyst with excellent enantiocontrol (up to 99:1 er). 10 This strategy was also successfully applied to the asymmetric synthesis of helically chiral analogs of loratadine, the active ingredient of Claritin (Scheme 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the enantioselective remote desymmetrization of diarylmethylamines enabled by chiral TM catalysts, the Miller group disclosed the remote desymmetrization of bis(pyridine)methylamines via asymmetric organocatalyzed pyridine N-oxidation in 2019 (Scheme 58 ). 92 A series of methylamines bearing bis(3-pyridyl) moieties ( 172 ) were examined under the asymmetric N-oxidation reaction with H 2 O 2 enabled by an aspartic acid containing peptide catalyst cat-58 , which gave access to the chiral monopyridine- N -oxide products 173 with good to high enantioselectivities. It is worth mentioning that the bulky N -pivaloyl group is critical to the high enantioselectivities of these reactions ( 173e ).…”
Section: Enantioselective Desymmetrizations Of Aminesmentioning
confidence: 99%